INFLUENCE OF PHYSICOCHEMICAL PROPERTIES OF SILVER NANOPARTICLES ON MAST CELL AND MACROPHAGE UPTAKE AND ACTVATION: ROLE OF SCAVENGER RECEPTOR B1 - Aldossari, Abdullah Ali (East Carolina University, 2018)
Silver nanoparticles (AgNPs) are widely used in consumer products and the medical field for their antimicrobial properties. Some studies reported toxic effects of AgNPs but cellular uptake of AgNPs and AgNP-induced inflammation pathways are still not fully understood. Mast cells and macrophages are essential players of innate and adaptive immune response against invading foreign materials. Mast cells and macrophages express various receptors to help in recognition and clearance of invading pathogens and foreign molecules. Scavenger receptors such as scavenger receptor B1 (SR-B1) expressed by different types of cells, play an important role in biomolecule transport such as cholesterol transport inside cells. In addition, SR-B1 has been reported to be a multi-ligand receptor and can interact with negatively charged molecules leading to uptake and activation of signaling pathways. The aim of this study was to investigate role of SR-B1 and influence of physicochemical properties of AgNPs on mast cell and macrophage AgNPs uptake and subsequent inflammatory responses. We assessed mast cell and macrophage uptake of different types of AgNPs that differ in shape, size, charge, coating, and suspension media. The physicochemical properties were found to influence levels of AgNPs uptake by mast cell and macrophage. In addition, inflammatory responses of mast cells and macrophages were found to be influenced by the physicochemical properties of AgNPs. Furthermore, SR-B1 was found to mediate AgNPs cellular uptake and influence the inflammatory response following AgNPs exposure. These findings have implications in understanding mechanisms of AgNPs toxicity. Further, these findings suggest that modifications of the physicochemical properties can help in targeting or avoiding specific receptors. Therefore, safer AgNPs can be produced and used in biomedical applications.
Keywords: Silver nanoparticles; Osteopontin; Membrane Glycoproteins; Receptors, Scavenger; Biological Transport; Macrophages; Silver; Mast Cells; Metal Nanoparticles